REAKTUALISASI KONSEP KEISLAMAN UNTUK MEMBANGUN INTEGRASI BANGSA (Kajian Ma’a>ni al-H}adi>th) - Ibnu Hajar Ansori, Roudlatunnasikah, Dinda Mar’atus S., dan Muhammad Agus Faisal (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2019)
Indonesian Islamic community is facing two unprofit concept. First, fundamentalism that has radical action. Second, liberalism that grows desakralization of religion. Those conditions have a big role to influence howthe sosiety act in religion, social, and politic. As a rahmah li al-‘alamin, Islam had offered a concept that full of solution from Rasulullah s alla Alla h ‘alaih wa sallama utterance. That concept gives someone’s Islamic indicator formula, not only be seen from identity, but also from their speak (lisan) and hands (yad). This article will explain the mean from utterance by integration-interconnection paradigm with communication psychology approachment and maudlu’i hadis. From this reseach, there’s an information that oral meaning is related in how to communicate, both of spoken or written. While yad meaning is a mufti’s knowledge, leader’s authorization, wealth of rich people, and prayers of the poor. That concept is related how someone’s speak and act well as their each proportion. By applying this concept, there is hoped Indonesia will be fair and prosperous country in God’s forgiveness.Keywords: Islamic Concept, Positive Communication, ProportionalAbstrak